2009
DOI: 10.1021/la803546r
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Silica Spheres: Synthesis and Mechanical Properties

Abstract: Core-shell polystyrene-silica spheres with diameters of 800 nm and 1.9 microm were synthesized by soap-free emulsion and dispersion polymerization of the polystyrene core, respectively. The polystyrene spheres were used as templates for the synthesis of silica shells of tunable thickness employing the Stöber method [Graf et al. Langmuir 2003, 19, 6693]. The polystyrene template was removed by thermal decomposition at 500 degrees C, resulting in smooth silica shells of well-defined thickness (15-70 nm). The ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
178
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(197 citation statements)
references
References 31 publications
13
178
0
6
Order By: Relevance
“…The synthesis of the core-shell particles by soap-free emulsion polymerization of the PS core (slightly copolymerized with divinylbenzene) and subsequent coating by silica is described elsewhere. [109] Here, it is shown that a relatively thin SiO 2 shell acts as a 'nano-armor' of the polymer core even in the molten state above its glass transition temperature while the particles retaining remarkably high mechanical strength.…”
Section: The Influence Of the Wave Vector: Suspensionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The synthesis of the core-shell particles by soap-free emulsion polymerization of the PS core (slightly copolymerized with divinylbenzene) and subsequent coating by silica is described elsewhere. [109] Here, it is shown that a relatively thin SiO 2 shell acts as a 'nano-armor' of the polymer core even in the molten state above its glass transition temperature while the particles retaining remarkably high mechanical strength.…”
Section: The Influence Of the Wave Vector: Suspensionsmentioning
confidence: 96%
“…[106,107] Furthermore, silica shells are much stiffer compared to most organic shells. [108,109] Here the rigidity of thin glassy silica shells is utilized for the realization of shape persistent polymer cores at temperatures well above the polymer glass transition temperature T g . In this section BLS is employed to investigate the shape-persistence of spherical core-shell colloids consisting of a soft polystyrene (PS) core with d=400±12 nm and a hard silica (SiO 2 ) nanoshell with thickness L=37±3 nm against heating; this size was determined by scanning electron microscopy, averaging over about 100 spheres.…”
Section: The Influence Of the Wave Vector: Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sacrificial core process is one of the most frequently used techniques to produce hollow inorganic spheres [1][2][3][4][5][6][7][8][9][10][11][12]. The sacrificial core approach involves the use of a solid organic or inorganic spherical particle as the template.…”
Section: Introductionmentioning
confidence: 99%
“…The core-shell structure is produced by coating the core with inorganic precursors or nanoparticles which are crosslinked to form the shell. Hollow spherical particles are subsequently generated by removing the template from the core-shell structure thermally [1][2][3][4][5][6][7][8][9][10] or chemically [1-3, 11, 12].…”
Section: Introductionmentioning
confidence: 99%